Islamic Popular Culture: Emerging of Nasyid Groups in Malaysia - Zulkiple Abd. Ghani (Universiti Sains Islam Malaysia, 2024)
This paper seeks to examine the emerging of nasyid's groups and their contributions in nurturing Islamic popular culture in Malaysia. In the light of the proliferation of da'wah, some nasyid groups have gradually emerged and grown, saying that they will uphold Islamic identity and propagate Islamic messages through the medium. Their songs fulfill a small amount of segment of radio and television time and regarded by some observe; as alternative entertainments to the non-Islamic culture. The groups objectives, visions and selected lyrics of their songs will be analyzed in order to present how they develop Islamic popular culture in facing globalism. This paper also argues that the major neglect of nourishing Islamic popular culture results in a vacuum which is inevitably Wed by non-Islamic culture. Therefore, as Malaysia is moving towards fulfilling Vision 2020 as a developed country which emphasizes on a fully moral and ethical society, artists, like other groups in society, have to have a model to build a good image. This role is being played by artists in nasyid groups.